Zircon in the Val Gardena sandstone from the Žirovski vrh and Sovodenj region, W Slovenia - Skaberne, Dragomir (Geologija, 1998)
The Val Gardena Formation of the Permian age in the Žiri region between Cerkno and Smrečje is one of more interesting formations in Slovenia because of occurrences of ore concentrations of uranium and copper. We tried to improve the lithofacial correlation by analysis of crystal forms of zircon. In the investigated Val Gardena sandstone, 37 different forms of zircon were found of the 64 types of the Pupin’s typologic classification. Correlation between different crystal forms of zircon is relatively low, and they cluster into seven groups. The lithostratigraphic members can be distinguished and correlated according to the zircon crystal forms with the mean certainty of 82 %. However, within the lithostratigraphic members the detailed correlation is uncertain at the present stage of our knowledge. The field of the most frequent zircon crystal forms S19 and S24 indicates the prevailing influence of orogenic types of igneous rocks of Ca-alkaline and K-Ca-alkaline composition between different igneous rocks in the source area.